Abraham : one nomad's amazing journey of faith - Swindoll, Charles R. (Carol Stream, Illinois : Tyndale House Publishers, Inc., 2014)
"When we rewind history back to Abraham?s era, we encounter people who concocted false superstitions to explain the unexplainable. Powerful kings claimed to be gods, building massive pyramids to achieve immortality. Out of this mass of misunderstandings, one man emerged. The man we know today as Abraham not only claimed that one true Creator existed but also staked his entire life on this belief. Why, thousands of years later, are we still discussing the faith of this desert nomad? One of America?s most popular Bible teachers, Pastor Chuck Swindoll, answers that question and many more in this compelling and insightful biography that will inspire your own faith." -- from publisher's website.
Includes bibliographical references.
Keywords: Abraham -- (Biblical patriarch)